Effectiveness of CorporateSocial Responsibility (CSR) to The Development of Micro, Small and Medium Enterprises (SMEs) - Dra. Dewi Andriany, M.M. (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
-